The Impact of Agricultural Support Policies in the United States and Other Major Countries : A Survey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper examines the recent difficulties experienced in U.S. agriculture, and discusses the role played by government policies, in particular reviewing recent developments in those policies. Studies of the extent and costs of agricultural protection in the United States and other major countries are surveyed and possible effects of multilateral reform of agricultural policies are discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet